2019
DOI: 10.3390/ma12010151
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Enriched Agglomerated Cork Material and Its Behaviour under Quasi-Static and Dynamic Loading

Abstract: The use of cork for a variety of applications has been gaining significance due to environmental concerns and political agendas. Consequently, its range of applications is growing rapidly. In this work, aiming to improve its mechanical response for crashworthiness applications, cork agglomerates were enriched by small quantities of graphene oxide or graphene nanoplates in order to observe a resulting improvement of the mechanical behaviour during quasi-static and dynamic compressive loading cases. To produce h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It has been highlighted that in VRUs impacts, head injuries are one of the most common injury types. A number of publications noted that brain deformation or strain is a principal mechanism of the head injury [60,77]. From the biomechanical perspective, head injuries are regarded as the consequence of a series of mechanical interactions of the complex multi-layered scalp-skull-meninges-CSF-BVs-brain system; the CSF is cerebrospinal fluid and BVs is the abbreviation of bridging veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been highlighted that in VRUs impacts, head injuries are one of the most common injury types. A number of publications noted that brain deformation or strain is a principal mechanism of the head injury [60,77]. From the biomechanical perspective, head injuries are regarded as the consequence of a series of mechanical interactions of the complex multi-layered scalp-skull-meninges-CSF-BVs-brain system; the CSF is cerebrospinal fluid and BVs is the abbreviation of bridging veins.…”
Section: Discussionmentioning
confidence: 99%
“…The last part of the presented authors' methodology is focused on safety gears and pro-active measuring systems. Moreover, the author presents, among others natural energy-absorbing materials-including cork-which, due to the adequate crashworthiness, may in the future replace commonly used polystyrene, for example, in motorcycle helmet liners [59][60][61].…”
Section: Author's Research Methodologymentioning
confidence: 99%
“…The continuous search for efficient and cost-effective materials to deal with crashworthiness applications has been driving many studies over recent decades [1][2][3][4][5][6][7][8][9][10][11][12]. However, recent self-consciousness and environmental responsibility are promoting the search for so-called green materials featuring good mechanical properties allied to recyclability and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…A material such as cork stands out to be employed as energy-absorbing liners in safety gear. Cork is a natural cellular material capable of absorbing great amounts of impact energy [10]. Jardin et al [14] performed quasi-static tests on different cork agglomerates and reported a value of 1.1 GJ/m 3 for a densified AC216 and 634 MJ/m 3 at the end of the stress plateau.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation